Local Culture and Rules as Competitive Strategic Predictor and the Impact on Real Estate Industry Performance in Indonesia - Selawa, Dewa Putu; Thoyib, Armanu; Ramantha, I Wayan; Djumahir, djumahir (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
Resources and operational environment of a company are known to have important role in its competitive strategic formulation. These three variables also found influencing business performance. However, little is known about the influence of an understanding toward local culture and rules where a company operated on competitive strategic formulation and the impact on business performance. This research is aimed to find out about the influence of an understanding and implementation of Tri Hita Karana as one of intangible strategic resources and the influence of local rules either in form of regional regulation or customary rules on competitive strategic formulation of real estate company operated in Indonesia, which is in Bali Province. In order to harmonize company with its environment through three dimensions based on Hindu philosophy (parahyangan as the manifestation of God dimension, pawongan as the manifestation of humanity dimension and palemahan as the manifestation of natural environment dimension), it is proven that understanding and implementation of Tri Hita Kirana have the highest influence from seven strategic resources formulation of a company. In addition, local rules also proven to significantly influence environmental dynamic faced by real estate companies operated in Bali. The research verified that resources owned by and environmental dynamics of a company have significant influence on competitive strategic that further influence business performance measured using Balance Score Card method.